How Buddhism might be propagated – ‘suffering is universal’ - Foster, Peter (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง; Vol 2 No 1 (2019): ปีที่ 2 ฉบับที่ 1 ประจำเดือนมกราคม - มิถุนายน 2562, 2019)
A long time ago, I read the Upanisa sutta ( Upanisa Sutta ) where the Buddha said, “In dependence on ‘Suffering’ arises ‘Faith’”.  With more than 7.5 billion humans in the world (2018), there’s a lot of suffering going on and a lot of potential for faith to arise. But, in my opinion people need to realise they are suffering to develop faith in a way out. And they also need to understand why they suffer in order to realise the way. Many people are unaware that they are suffering at all. These people are unlikely to feel the need to change. The Buddha considered whether such people would be able to understand what he’d realised and it was only the words “There are beings with little dust in their eyes who are falling away because they do not hear the Dhamma”( Ayatana Sutta)  that persuaded him to try and teach others. Often those that feel suffering think it is because they don’t have enough money to buy something or something they have has broken – usually it is something material or even a relationship. But the Buddha said that the “Cause of suffering is ‘craving’( Ayatana Sutta ) This makes complete sense to me if we think of it as “I want things to be different to the way they are”. If we are not satisfied with things as they are, we suffer. It seems so blatantly obvious that it’s almost crazy to even discuss it.